Immunotropic effects of nitrogenous metabolites (creatinine, urea, uric acid and bilirubin) in humans exposed to the factors of the accident at the Chоrnobyl nuclear power plant - Igor Kuchma; Anatoliy Gozhenko; Volodymyra Bilas; Sofiya Ruzhylo; Galyna Kovalchuk; Yaryna Nahurna; Walery Zukow; Igor Popovych (Kazimierz Wielki University, 2020)
Background. In previous studies, we found that nitrogenous metabolites exhibit significant immunotropic activity, both suppressor and enhancing, at healthy rats. The purpose of this and our subsequent research is to elucidate the links between nitrogenous metabolites and immune parameters in different categories of people, both healthy and sick. Material and methods. The object of observation in 1997 were 19 men and 3 women who were exposed to pathogenic factors of the accident at the Chоrnobyl nuclear power plant during the liquidation of its consequences in 1986-87. The survey was conducted twice - on admission and after two weeks of rehabilitation at the Truskavets' Spa. The plasma and urinary concentration of the nitrogenous metabolites were determined. Immune status was assessed on tests of I and II levels according to the WHO memorandum. Results. Both negative and positive metabolic-immune correlations were revealed. Calculation of multiple correlation coefficients between individual metabolite parameters and constellations of immune parameters revealed the maximum immunotropic effect of Urea urine (R=0,756). This is followed by Uric acid plasma (R=0,727) and urine (R=0,691), Urea plasma (R=0,622), Creatinine plasma (R=0,588), Bilirubinemia (R=0,546) and Creatinine urine (R=0,510). The canonical correlation between the constellation of nitrogenous metabolites, on the one hand, and the parameters of immunity, on the other hand, was very strong: R=0,971; χ2(15)=239; p<10-5. Conclusion. Nitrogenous metabolites have immunomodulatory effects, both suppressor and enhancing, both in healthy rats and in humans exposed to pathogenic influences.